Capacitance Effects Superimposed on Redox Processes in Molecular‐Cluster Batteries: A Synergic Route to High‐Capacity Energy Storage. Issue 34 (12th July 2013) - Wang, Heng; Zeng, Zhaoyang; Kawasaki, Naoya; Eckert, Hellmut; Yoshikawa, Hirofumi; Awaga, Kunio
Abstract Rechargeable molecular‐cluster batteries (MCBs) based on the manganese cluster complex [Mn12O12(CH3CH2C(CH3)2COO)16(H2O)4] ([Mn12]) that exhibited a capacity of approximately 200 A h kg−1 in the battery voltage range of 4.0 to 2.0 V were developed. In these batteries, the capacity of approximately 100 A h kg−1 in the range of 4.0–3.0 V is caused by a chemical reduction from [Mn12]0 to [Mn12]8−, whereas the other half in the range of 3.0–2.0 V cannot be explained by a redox change of the Mn ions. We performed the cyclic voltammetry (CV) and 7Li solid‐state NMR measurements on the Mn12‐MCBs to investigate the origin of the capacity below 3.0 V. Pseudo‐rectangular‐shaped CV curves in the range of 3.0–2.0 V demonstrate the presence of an electrical double‐layer (EDL) capacitance in Mn12‐MCBs, which corresponds to approximately 100 A h kg−1. 7Li NMR studies suggest that Li ions form an EDL with electrons in carbon black electrodes in the capacitance voltage range. The capacitance effects are not formed by the single‐carbon electrodes alone, but appear only in the mixture of Mn12 and the carbon black electrodes. This type of coexistence of capacitance effects and redox reaction in one electrochemical cell is quite unusual and can serve as a new working principle for high‐performance energy‐storage devices.